Multi-degree-of-freedom coupling dynamic characteristic of TBM disc cutter under shock excitation - Huo, Jun-zhou; Sun, Xiao-long; Li, Guang-qing; Li, Tao; Sun, Wei (Journal of Central South University, 2015)
When the tunneling boring machine (TBM) cutterhead tunnels, the excessive vibration and damage are a severe engineering problem, thereby the anti-vibration design is a key technology in the disc cutter system. The structure of disc cutter contains many joint interfaces among cutter ring, cutter body, bearings and cutter shaft. On account of the coupling for dynamic contact and the transfer path among joint interface, mechanical behavior of disc cutter becomes extremely complex under the impact of heavy-duty, which puts forward higher requirements for disc cutter design. A multi-degree-of-freedom coupling dynamic model, which contains a cutter ring, a cutter body, two bearings and cutter shaft, is established, considering the external stochastic excitations, bearing nonlinear contact force, multidirectional mutual coupling vibration, etc. Based on the parameters of an actual project and the strong impact external excitations, the modal properties and dynamic responses are analyzed, as well as the cutter shaft and bearings’ loads and load transmission law are obtained. Numerical results indicate the maximum radial and axial cutter ring amplitudes of dynamic responses are 0.568 mm and 0.112 mm; the maximum radial and axial vibration velocities are 41.1 mm/s and 38.9 mm/s; the maximum radial and axial vibration accelerations are 94.7 m/s 2 and 58.6 m/s 2 ; the maximum swing angle and angular velocity of cutter ring are 0.007° and 0.0074 rad/s, respectively. Finally, the maximum load of bearing roller is 40.3 kN. The proposed research lays a foundation for structure optimization design of disc cutter and cutter base, as well as model selection, modification and fatigue life of the cutter bearing.